2014
DOI: 10.1536/ihj.13-221
|View full text |Cite
|
Sign up to set email alerts
|

Urine Sodium Excretion After Tolvaptan Administration Is Dependent Upon Baseline Serum Sodium Levels

Abstract: SummarySeveral studies have demonstrated that tolvaptan (TLV) can improve hyponatremia in advanced heart failure (HF) patients with rare chance of hypernatremia. However, changes in serum sodium concentrations (S-Na) in patients with or without hyponatremia during TLV treatment have not been analyzed.Ninety-seven in-hospital patients with decompensated HF who had received TLV at 3.75-15 mg/day for 1 week were enrolled. Among 68 "responders", who had achieved any increases in urine volume (UV) during the fi rst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…To better elucidate the potential mechanisms, and to possibly provide clinicians with predictors of the response to Tolvaptan, we searched for variables associated to the degree of the effect. As already reported [ 23 , 33 , 45 ], baseline [Na + ] was negatively associated with the subsequent rise in [Na + ] resulting from treatment, i.e., the lower the baseline [Na + ], the bigger the response. This could merely reflect the fact that subjects with higher baseline [Na + ] have less room for improvement, and likely reflect a lower degree of AVP activation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…To better elucidate the potential mechanisms, and to possibly provide clinicians with predictors of the response to Tolvaptan, we searched for variables associated to the degree of the effect. As already reported [ 23 , 33 , 45 ], baseline [Na + ] was negatively associated with the subsequent rise in [Na + ] resulting from treatment, i.e., the lower the baseline [Na + ], the bigger the response. This could merely reflect the fact that subjects with higher baseline [Na + ] have less room for improvement, and likely reflect a lower degree of AVP activation.…”
Section: Discussionsupporting
confidence: 67%
“…Vaptans are a recently introduced class of vasopressin V2-receptor antagonists, yielding to an increased electrolyte-free water excretion and, thus, increased serum sodium concentration [ 22 ]. Several studies showed their safety and effectiveness in hyponatremia with preserved total body sodium pool in different categories of patients [ 17 , 23 27 ]; however, the experience with these drugs is limited in the critical care setting. After positive initial experience with oral Tolvaptan in single cases [ 28 , 29 ], we sought to analyze our case series to investigate the short-term outcomes on water and electrolyte balance for patients prescribed oral vaptans for hyponatremia with preserved total body sodium pool within our ICU.…”
Section: Introductionmentioning
confidence: 99%
“…The change in the Na level is correlated with the serum Na level prior to receiving tolvaptan ( 22 , 23 ). In 2016, Hirai et al evaluated the risk of hypernatremia; a baseline Na level of ≥140 mEq/L, initial tolvaptan ≥7.5 mg/day, and a serum BUN/Cr ratio of ≥20 were independent risk factors for early-onset hypernatremia, particularly in elderly patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms of this efficacy could be considered. First, natriuretic effects of tolvaptan have been demonstrated via the decreases in sodium reabsorption against the effect of vasopressin with the activation of epithelial Na-channels in the distal nephron [ 32 , 33 ]. Second, tolvaptan restored reportedly podocyte injury in nephrotic rats [ 34 ], which had intraglomerular hypertension by podocyte injury via activation of vasopressin.…”
Section: Discussionmentioning
confidence: 99%